Blue Screen Blue Mood: Investigating the Association of Daily Screen Time with Sleep Quality and Mental Distress in Students - Marvi Talpur (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: The pervasive influence of technology on daily life, particularly through screens, and its implications for sleep quality and mental health are critical. Objective(s): To evaluate the daily screen time of students from different fields of study and to assess its association with demographic variables as well as sleep quality and mental health symptoms. Materials and Methods: This Cross-sectional study was conducted in Isra University, Hyderabad, from August 2023 to February 2024, in an academic setting among undergraduate students. A total of 152 participants who provided informed consent and were enrolled in academic programs were included in the study. Individuals with diagnosed psychiatric conditions or sleep disorders were excluded. Data regarding demographic details, sleep quality, mental distress, and daily screen time was collected after informed consent, using self-administered printed questionnaires. Standardized tools used included the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, and the Depression Anxiety Stress Scale (DASS-42) to evaluate mental distress. Statistical analysis, conducted using SPSS (version 22), determined correlations between daily screen time, PSQI, and DAS scores (p≤0.05, 95% confidence). Results: The mean age of the participants was 20.59±2.16 years. The vast majority of participants belonged to urban areas (87.5%) and were day scholars (74.34%). The mean daily screen time of the study participants was found to be 5.85±1.14 hours. The mean scores of depression, anxiety, stress, and PSQI were found to be 13.34±12.01, 11.17±9.41, 15.32±11.09, and 6.45±3.48, respectively. There was a statistically significant positive correlation observed between screen time and depression (r = 0.81, p < 0.01), anxiety (r 0.78, p < 0.01), stress (r = 0.83, p < 0.01), and PSQI (r = 0.75, p < 0.01). Conclusion: Increased screen time was associated with poorer sleep quality and higher levels of mental distress. Keywords: Screen Time; Mental Health; Sleep Quality; Depression; Anxiety.